2016
DOI: 10.1371/journal.pone.0156570
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of the Psychopathic Personality Inventory-Revised in a Swedish Non-Criminal Sample – A Multimethod Approach including Psychophysiological Correlates of Empathy for Pain

Abstract: Cross-cultural investigation of psychopathy measures is important for clarifying the nomological network surrounding the psychopathy construct. The Psychopathic Personality Inventory-Revised (PPI-R) is one of the most extensively researched self-report measures of psychopathic traits in adults. To date however, it has been examined primarily in North American criminal or student samples. To address this gap in the literature, we examined PPI-R’s reliability, construct validity and factor structure in non-crimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
3
12
0
Order By: Relevance
“…
Figure 11.( a – d ) Empathy for pain: personality predictors. Associations between PPI subscales and empathic responding have been reported previously [57].
…”
Section: Resultssupporting
confidence: 55%
“…
Figure 11.( a – d ) Empathy for pain: personality predictors. Associations between PPI subscales and empathic responding have been reported previously [57].
…”
Section: Resultssupporting
confidence: 55%
“…Lorber concluded that HR was mostly related to aggression, while EDA was most prominently associated with psychopathy (especially lower rest EDA and reactivity in psychopathy samples). Consensus on the exact core features of psychopathy is lacking, but psychopathy is typically characterized by problems in affective, behavioral, and interpersonal functioning, which increases the psychopath's risk for violent behavior (Sörman et al, ). Lastly, the fourth review by Patrick () reported a higher HR and EDA reactivity to stressful events, interpersonal stressors, in particular, and in samples of hostile‐aggressive adults.…”
Section: Introductionmentioning
confidence: 99%
“…It is encouraging that although investigations of measures of psychopathy were initially confined to samples of young adults, with some specifically screening out older adults, more recent research has used samples with wider age ranges (Christian & Sellbom, 2016;Collison, Miller, Gaughn, Widiger, & Lynam, 2016;Gordts, Uzieblo, Neumann, Bussche, & Rossi, 2015;Sörman et al, 2016). These later psychometric evaluations of measures of psychopathy apparently support their reliability and validity across a wide age range, but still none examine the small, older groups separately; it remains unclear whether these measures are valid and reliable tools for screening psychopathy in older adults.…”
Section: Discussionmentioning
confidence: 99%